Soluble epoxide hydrolase inhibitor can protect the femoral head against tobacco smoke exposure-induced osteonecrosis in spontaneously hypertensive rats. (15th January 2022) - Xu, Jingyi; Qiu, Xing; Yu, Gary; Ly, Maria; Yang, Jun; Silva, Rona M; Zhang, Xun; Yu, Mang; Wang, Yinong; Hammock, Bruce; Pinkerton, Kent E.; Zhao, Dewei
Abstract: Exposure to tobacco smoke (TS) has been considered a risk factor for osteonecrosis of the femoral head (ONFH). Soluble epoxide hydrolase inhibitors (sEHIs) have been found to reduce inflammation and oxidative stress in a variety of pathologies. This study was designed to assess the effect of sEHI on the development of ONFH phenotypes induced by TS exposure in spontaneously hypertensive (SH) rats. SH and normotensive Wistar Kyoto (WKY) rats were exposed to filtered air (FA) or TS (80 mg/m3 particulate concentration) 6 h/day, 3 days/week for 8 weeks. During this period, sEHI was delivered through drinking water at a concentration of 6 mg/L. Histology, immunohistochemistry, and micro-CT morphometry were performed for phenotypic evaluation. As results, TS exposure induced significant increases in adipocyte area, bone specific surface (BS/BV), and trabecular separation (Tb.SP), as well as significant decreases in bone mineral density (BMD), percent trabecular area (Tb.Ar), HIF-1a expression, bone volume fraction (BV/TV), trabecular numbers (Tb.N), and trabecular thickness (Tb.Th) in both SH and WKY rats. However, the protective effects of sEHI were mainly observed in TS-exposed SH rats, specifically in the density of osteocytes, BMD, Tb.Ar, HIF-1a expression, BV/TV, BS/BV, Tb.N, and Tb.SP. Our study confirms that TS exposure can induce ONFH especially in SH rats, and suggests that sEHI therapy may protect against TS exposure-induced osteonecrotic changes in the femoral head.